Overprotected Politicians - Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2007)
This paper argues that politicians are overprotected. The costs of political assassination differ systematically depending on whether a private or a public point of view is taken. A politician attributes a very high (if not infinite) cost to his or her survival. The social cost of political assassination is much smaller as politicians are replaceable. Conversely, the private cost of the security measures is low for politicians, its bulk - including time loss and inconvenience - is imposed on taxpayers and the general public. The extent of overprotection is larger in dictatorial than in democratic countries.
Keywords: D01; D70; H50; J28; Z10; 330; Politicians; rational choice; assassination; security; democracy; dictatorship